Preemptive‐TIPS Improves Outcome in High‐Risk Variceal Bleeding: An Observational Study. Issue 1 (10th December 2018) - Hernández‐Gea, Virginia; Procopet, Bogdan; Giráldez, Álvaro; Amitrano, Lucio; Villanueva, Candid; Thabut, Dominique; Ibañez‐Samaniego, Luis; Silva‐Junior, Gilberto; Martinez, Javier; Genescà, Joan; Bureau, Christophe; Trebicka, Jonel; et al.
Abstract : Patients admitted with acute variceal bleeding (AVB) and Child‐Pugh C score (CP‐C) or Child‐Pugh B plus active bleeding at endoscopy (CP‐B+AB) are at high risk for treatment failure, rebleeding, and mortality. A preemptive transjugular intrahepatic portosystemic shunt (p‐TIPS) has been shown to improve survival in these patients, but its use in clinical practice has been challenged and not routinely incorporated. The present study aimed to further validate the role of preemptive TIPS in a large number of high‐risk patients. This multicenter, international, observational study included 671 patients from 34 centers admitted for AVB and high risk of treatment failure. Patients were managed according to current guidelines, and use of drugs and endoscopic therapy (D+E) or p‐TIPS was based on individual center policy. p‐TIPS in the setting of AVB is associated with a lower mortality in CP‐C patients compared with D+E (1 year mortality 22% vs. 47% in D+E group; P  = 0.002). Mortality rate in CP‐B+AB patients was low, and p‐TIPS did not improve it. In CP‐C and CP‐B+AB patients, p‐TIPS reduced treatment failure and rebleeding (1‐year cumulative incidence function probability of remaining free of the composite endpoint: 92% vs. 74% in the D+E group; P  = 0.017) and development of de novo or worsening of previous ascites without increasing rates of hepatic encephalopathy. Conclusion: p‐TIPS must be the treatment of choice in CP‐C patients with AVB. Because of the strong benefit in preventing further bleeding and ascites, p‐TIPS could be a good treatment strategy for CP‐B+AB patients.